Mammals, amphibians, and reptiles of Costa Rica : a field guide - Henderson, Carrol L. (Corrie Herring Hooks series, 2010)
To help visitors, as well as local residents, identify and enjoy the wildlife of Costa Rica, Carrol L. Henderson published Field Guide to the Wildlife of Costa Rica in 2002, and it instantly became the indispensable guide. Now Henderson has created a field guide dedicated to the monkeys, sloths, treefrogs, lizards, crocodiles, and other animals that travelers are most likely to see while exploring the wild lands of Costa Rica. He includes fascinating information on their natural history, ecology, identification, and behavior gleaned from his forty years of travels, studies, and wildlife viewing in Costa Rica, as well as details on where to see these remarkable and beautiful creatures. The mammals, amphibians, and reptiles are illustrated by stunning and colorful photographs?most of which were taken in the wild by Henderson. A detailed and invaluable appendix that identifies many of Costa Rica's best wildlife-watching destinations, lodges, and contact information for trip-planning purposes completes the volume.